Mutations in COQ8B (ADCK4) found in patients with steroid‐resistant nephrotic syndrome alter COQ8B function. Issue 3 (18th December 2017) - Vazquez Fonseca, Luis; Doimo, Mara; Calderan, Cristina; Desbats, Maria Andrea; Acosta, Manuel J.; Cerqua, Cristina; Cassina, Matteo; Ashraf, Shazia; Hildebrandt, Friedhelm; Sartori, Geppo; Navas, Placido; Trevisson, Eva; et al.
Abstract: Mutations in COQ8B cause steroid‐resistant nephrotic syndrome with variable neurological involvement. In yeast, COQ8 encodes a protein required for coenzyme Q (CoQ) biosynthesis, whose precise role is not clear. Humans harbor two paralog genes: COQ8A and COQ8B (previously termed ADCK3 and ADCK4 ). We have found that COQ8B is a mitochondrial matrix protein peripherally associated with the inner membrane. COQ8B can complement a ΔCOQ8 yeast strain when its mitochondrial targeting sequence (MTS) is replaced by a yeast MTS. This model was employed to validate COQ8B mutations, and to establish genotype–phenotype correlations. All mutations affected respiratory growth, but there was no correlation between mutation type and the severity of the phenotype. In fact, contrary to the case of COQ2, where residual CoQ biosynthesis correlates with clinical severity, patients harboring hypomorphic COQ8B alleles did not display a different phenotype compared with those with null mutations. These data also suggest that the system is redundant, and that other proteins (probably COQ8A) may partially compensate for the absence of COQ8B. Finally, a COQ8B polymorphism, present in 50% of the European population (NM_024876.3:c.521A > G, p.His174Arg), affects stability of the protein and could represent a risk factor for secondary CoQ deficiencies or for other complex traits. Abstract : Mutations in COQ8B cause steroid‐resistant nephrotic syndrome. In yeast, COQ8 encodes a protein required for coenzyme Q biosynthesis. COQ8B encodes a mitochondrial matrix protein peripherally associated with the inner membrane and it can complement a ΔCOQ8 yeast strain when its mitochondrial targeting sequence (MTS) is replaced by a yeast MTS. When expressed in yeast, all patients alleles affected respiratory growth, without a clear correlation between mutation type and the severity of the phenotype.